The Co-operative College and a Century of Social Change Internationalism, Co-operativism and Learning - Woodin, Tom.; Vernon, Keith; Shaw, Linda; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BThis well written book explores the pivotal role that the Co-operative College has played in the development of cooperative education in Britain and beyond on a global scale. The narrative intertwines the immediate practical requirements of cooperatives with broader, visionary perspectives, illustrating how education within cooperatives is intricately linked to their operational success and sustainability.(3y (B- Simel Esim, Head, Cooperative, Social and Solidarity Economy Unit, International Labour Organisation (ILO) (3z(BThe Co-operative College has had a profound impact on the lives of generations of students. This impressive, lucidly written study makes a compelling case for both its national and global importance.(3y (B- Peter Gurney, Professor, University of Essex, UK This open access book explores the Co-operative College$1 (Bs distinctive adult educational tradition over the past century as it provided education for co-operative leaders, employees and members in addition to developing a range of wider educational initiatives and ideas internationally. The Co-operative College is a British educational charity established in 1919, founded on co-operative principles. It played a crucial role in co-operative education in the British Empire and subsequently in the independent nations. In doing so, it brought together vocational and liberal education as well as educating members as part of a movement that fostered significant social change. It draws on original archival research at the National Co-operative Archive in Manchester as well as other material at the National Archives, Bishopsgate Institute and the British Library. Furthermore, the rich archives of the National Co-operative Archive allow for the development of a rich visual history of the movement to be explored. Tom Woodin is Professor in the Social History of Education at the Institute of Education, University College London, UK. Keith Vernon is Principal Lecturer in History at the University of Central Lancashire, UK. Linda Shaw was the Vice Principal at the Co-operative College in Manchester, UK.s
Introduction -- Beginnings -- The Formation of the Co-operative College and the Interwar Years -- War and Peace -- A Short Golden Age? The Post-War Years -- Challenge, Engagement and Decline, 1958-1977 -- Decline, Crisis and Renewal, 1977-1999 -- Searching for a New Identity, 2000-2019 -- Conclusion.
Keywords: Education; Education -- History; Social history; School management and organization; School administration; Education and state; Education; History of Education; Social History; Organization and Leadership; Educational Policy and Politics